Hydatid Cyst Disease of the Thyroid Gland: Report of Two Cases - Akbulut, Sami (Int Surg, 2015)
Hydatid cyst disease may develop in any organ of the body, most frequently in the liver and lung, but occasionally can affect other organs such as the thyroid gland. Although the prevalence of thyroidal cyst disease varies by region, literature data suggest that it ranges between 0% and 3.4%. The aim of this report was to share 2 cases with thyroid hydatid cyst. Two female patients aged 26 and 57 years were admitted to our outpatient clinic with different complaints. While the first case presented with front of the neck swelling and pain, the second case presented with hoarseness, sore throat, and neck swelling. Both patients were living in a rural area in the southeastern region of Turkey and had had a long history of animal contact. Both patients had undergone previous surgeries for hydatid cyst disease. Both patients presented with a clinical picture consistent with typical multinodular goiter, and both underwent total thyroidectomy after detailed examinations and tests. The exact diagnosis was made after histopathologic examination in both patients. They both had a negative indirect hemagglutination test studied from blood samples. They both have had no recurrences during a 4-year follow-up. In conclusion, although thyroid gland is rarely affected, hydatid cyst disease should not be overlooked in differential diagnosis of cystic lesions of thyroid gland in patients who live in regions where hydatid cyst disease is endemic and who had hydatid cysts in other regions of their body.